2016
DOI: 10.24002/kinerja.v20i2.843
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Mempengaruhi Kualitas Laporan Keuangan Pemerintah Daerah Kota Semarang

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1
24

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 0 publications
2
13
1
24
Order By: Relevance
“…Research gap also occurs on research variable of regional financial accounting system as evidenced by Ratifah (2012); Evicahyani (2016); Juwita (2013); and Sanjaya (2017) has a positive effect on the quality of local government financial statements. This is in contrast to Setyowati et al(2016) and Rahmadani (2015) who did not find the relationship between the regional financial accounting system and the quality of local government financial statement.…”
Section: Introductioncontrasting
confidence: 96%
“…Research gap also occurs on research variable of regional financial accounting system as evidenced by Ratifah (2012); Evicahyani (2016); Juwita (2013); and Sanjaya (2017) has a positive effect on the quality of local government financial statements. This is in contrast to Setyowati et al(2016) and Rahmadani (2015) who did not find the relationship between the regional financial accounting system and the quality of local government financial statement.…”
Section: Introductioncontrasting
confidence: 96%
“…Pelaporan keuangan pemerintah bertujuan untuk menyajikan dan menyediakan informasi yang bermanfaat dan dapat digunakan sebagai dasar pegambilan keputusan, sebagai suatu bentuk pertanggungjawaban kepada masyarakat, dan menilai kinerja maupun kondisi organisasi (Setyowati, Isthika, dan Pratiwi, 2016 (Rama dan Jones, 2008). Sistem informasi yang dikelola dengan baik mendukung pelaporan dan penyusunan laporan keuangan yang sesuai dengan peraturan yang berlaku (Saputra, 2015).…”
Section: Laporan Keuangan Pemerintah (Daerah)unclassified
“…Competent human resources are the key to building and maintaining muzaki trust based on the financial reports that HR compiles and presents. Based on previous research conducted by [26] and [31] it can be concluded that HR competencies have a positive and significant effect on the quality of financial statements. Meanwhile, a different conclusion was expressed by [17] who concluded that human resource competence partially had no significant effect on the quality of financial statements.…”
Section: Introductionmentioning
confidence: 96%
“…Based on previous research stated by [22] the use of IT affects the quality of financial reports. However, contradictory results are stated by [1] and [26] where they reveal that the use of IT has no effect on the quality of financial statements.…”
Section: Introductionmentioning
confidence: 96%